Experimental Study on Flame‒Flame Interaction and Its Merging Features Induced by Double Rectangular Propane Diffusion Burners With Various Aspect Ratios. Issue 8 (3rd August 2019) - Tao, Changfa; Ye, Qingpan; Wei, Jiangjun; Shi, Qin; Tang, Fei
ABSTRACT: An experimental study is conducted to reveal the flame‒flame interaction (including completely continuous merging phenomenon, intermittent merging phenomenon, and non-merging phenomenon) of and the merging flame length of double propane diffusion flame with various aspect ratios, and its influence is measured in terms of the fire heat release rates, separate spaces between rectangular sources and different pool aspect ratios (1:1, 1:2, 1:4, and 1:8). The flames merging behaviors are recorded by a charge-coupled device (CCD) camera. The merging probability of double propane diffusion flame is found to increase with the increasing of the heat release rate and the pool aspect ratio. A correlation has been developed to estimate the merging probability of the double propane diffusion flame under different aspect ratios and separate spaces. The correlation is proposed to describe the merging flame length of two rectangular diffusion flames with various aspect ratios, which is an inverse proportional function of dimensionless heat release rate.